A Case study on the symptoms, history and developmental measures of school-aged children with attention deficit hyperactivity disorder (ADHD) - Fernandez, Johanna
This study is concerned about the cases of three school-aged children with ADHD(Attention Deficit Hyperactivity Disorder) from Ebenezer Christian School, Davao City. ADHD is a behavioral disorder that may begin in early childhood and often lasts through adolescence and adulthood. Children with ADHD consistently have short attention spans, difficulty controlling their impulses, and are often physically restless. Since no one yet knows the true cause of ADHD, this study attempted to determine the general symptoms of complaints on the three areas of the children's life- health, family and school. This study also verified on the details of the family history of these children so as to prove any possible theories regarding the common factors and conditions associated with ADHD. It also investigated considerable evidences on which between environmental factors or genetic factors had more to do with the cause of the disorder. This study also bore out developmental courses and treatment in managing the behavior of an ADHD child. The primary method used in this study is the interview method. These cases were analyzed and the respondents of the study include the children diagnosed with ADHD, their parents and their teachers. Inattention, impulsiveness, mood and energy swings, and aggressiveness are evidently common to these children. Pre-natal diet, social or environmental factors do not mainly seem to cause ADHD. But maintaining a good and consistent relationship between the child and his parents/teachers is very important. Coping ADHD through counseling, school intervention, behavior management and medication were provided so as to comprehend how to effectively deal with the condition.
Thesis, Undergraduate (BA Social Science) -- U. P. in Mindanao